Chloroplast genomic data provide new and robust insights into the phylogeny and evolution of the Ranunculaceae - Zhai, Wei; Duan, Xiaoshan; Zhang, Rui; Guo, Chunce; Li, Lin; Xu, Guixia; Shan, Hongyan; Kong, Hongzhi; Ren, Yi (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Chloroplast (cp) genomes of 35 species representing 31 genera of the 14 tribes of the Ranunculaceae were sequenced, based on which well-resolved phylogenetic trees were obtained.•Two waves of radiation within the core Ranunculaceae were identified, through which most of the extant tribes and genera were generated.•Many of the characters that were once widely used for systematic considerations were actually results of parallel, convergent or reversal evolution.•Frequent inversions, duplications, or losses of fragments have contributed to cp genome evolution. The family Ranunculaceae, a member of early-diverging eudicots that is increasingly being used as a model for the study of plant developmental evolution, has been the focus of systematic studies for centuries. Recent studies showed that the family can be divided into 14 tribes, with Glaucideae, Hydrastideae, and Coptideae being the successive basal-most lineages. The relationships among the remaining 11 tribes, however, remain controversial, so that a clear picture of character evolution within the family is still lacking. In this study, by sequencing, assembling and analyzing the chloroplast (cp) genomes of 35 species representing 31 genera of the 14 tribes, we resolved the relationships among the tribes and genera of the Ranunculaceae and clarified several long-standing controversies. We found that many of the characters that were once widely used for taxonomic and systematic considerations were actually results of parallel, convergent or even reversal evolution, suggestive of unreliability. We also found that the family has likely experienced two waves of radiative evolution, through which most of the extant tribes and genera were generated. Notably, both waves of radiation were correlated with the increase in the temperature of the earth, suggesting that global warming may have been the driving force of the radiation events. Based on these observations, we hypothesize that global warming and the associated decrease in the type and number of animal pollinators may have been the main reason why taxa with highly elaborate petals as well as those without petal were generated during each of the two waves of radiation.